Jednostka a wspólnota w filozofii Charles’a Taylora - Kopyciński, Maciej (Filozofia Chrześcijańska, 2015)
In my article I analyse relation of individual and community in Charles Taylor’s philosophy. This relation is presented on two problematic levels. On the first level he concentrates on political philosophy and the second one relates to subject and language. In his political philosophy Charles Taylor starts from liberal – communitarian debate which is a basis for his own position, so-called holistic individualism. It means that on the ontological level individual is unavoidable involved in bonds of community but on the level of preferences individualism is highly valued. On the second level Taylor tries to break extremes of structuralism and idealism. In this case he refers to hermeneutic philosophy and shows the subject as a dialogical one and as a co-author of rules which determine himself. Translated by Agata Miętek